2015
DOI: 10.3139/120.110717
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of industrial conditions during multi-stage cooling of C70D high-carbon steel wire rod

Abstract: An analysis of the parameters of multi-stage controlled strip cooling during the process of rolling of 5.5 mm-diameter C70D high-carbon steel wire rod has been made in this publication. Investigations included also the analysis of the flow rate of the cooling medium and its pressure in the devices for accelerated and controlled cooling of the strip directly in the rolling line, as well as in the STELMOR line. The investigations carried out within the study have determined the cooling capacity of the accelerate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 2 publications
0
10
0
Order By: Relevance
“…That is why laboratory rolling mills are constructed to illustrate the conditions of the real rolling process in a more detailed way. An example of the above mentioned test can be semi-industrial simulation of manufacturing processes of alloys and metal products (LPS) in IMŻ Gliwice (Institute for Ferrous Metallurgy) [2] and semi-continuous laboratory mill for rolling bars in VSB -Technical University of Ostrava, Faculty of Metallurgy and Materials Engineering, Czech Republic [3]. Potential applications of semi-continuous laboratory are simulations of industrial rolling conditions, choice of optimal process parameters and regulated cooling of steel and alloys non-ferrous alloys.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…That is why laboratory rolling mills are constructed to illustrate the conditions of the real rolling process in a more detailed way. An example of the above mentioned test can be semi-industrial simulation of manufacturing processes of alloys and metal products (LPS) in IMŻ Gliwice (Institute for Ferrous Metallurgy) [2] and semi-continuous laboratory mill for rolling bars in VSB -Technical University of Ostrava, Faculty of Metallurgy and Materials Engineering, Czech Republic [3]. Potential applications of semi-continuous laboratory are simulations of industrial rolling conditions, choice of optimal process parameters and regulated cooling of steel and alloys non-ferrous alloys.…”
Section: Introductionmentioning
confidence: 99%
“…Low-carbon steel types intended for cold-upsetting are rolled in modern continuous systems [1,2]. Linear velocity of rolling wire rod in such systems equals up to 100 m/s.…”
Section: Introductionmentioning
confidence: 99%
“…Issues related to improving wire rod quality have been dealt with by the authors of papers [4][5][6][7][8][9][10][11][12][13]. In [5], several groups of steel for wire rod production were characterized, such as interstitial free, ferritic/martensitic and micro-alloyed pearlite steels.…”
Section: Introductionmentioning
confidence: 99%
“…The authors of this work showed that from the point of view of the area of application of the obtained wire rod, it is important to significantly increase the capacity for further, direct cold processing. Works [4,[6][7][8][9][10][11]13] relate to the rolling processes of high carbon steel. In these works, the effect of the temperature and cooling conditions on the microstructure and properties of wire rod were analysed.…”
Section: Introductionmentioning
confidence: 99%
“…High-carbon steel types for wire rod are rolled in modern continuous systems [1,2]. Linear velocity of rolling wire rod in such systems equals up to 120 m/s.…”
Section: Introductionmentioning
confidence: 99%